The effects of flow rates on the recovery of L-(+)-lactic acid using powdered activated carbon (PAC) - Loong, Li Juan (Universiti Malaysia Sarawak (UNIMAS), 2007)
The effects of flmv rates on the recovery of L-(+)-lactic acid using Powdered Activated Charcoal (PAC) was studied at three different flow rates (8 mLlhr, 12 rnLlhr, 16 mLlhr) compared to adsorption under gravity (l mLlhr). In this study, it was observed that the fastest flow rate (16 mLlhr) shows the highest percentages of lactic acid recovery (96.31 ± 0.02 %), glucose (35.32 ± 7.93 %) and (89.61 ± 0.06 °/~) proteins removaJ compared to 12mLlbr. SmLlhr and I mLlhr flow rates